Physiological Rhythms, Processes, and Adaptations of Arctic Mammals. Part II. Final Report for 1971 (Including Spring, 1972) - Folk,G. Edgar , Jr (1972)
Four years (1966-1971) of research on the physiological rhythms, processes, and adaptations of arctic mammals is summarized (Part I) and detailed attention is given to 1971-72 activities (Part II). Study of the seasonal as well as the daily physiological changes has been carried out; and the concept of interacting adaptations has been developed, with emphasis on radio telemetry. An extensive bibliography of publications which have arisen from this project is included, as are several of the articles themselves. (Author) See also Part 1, AD-748 633.